Association between pets and dry eye symptoms: a Chinese national-based study - Kai, Jia-Yan (2024)
Background: Pet-derived allergens are another source of indoor air pollution that could affect human health. However, the association between pet ownership and the risk of dry eye symptoms (DES) remains to be elucidated. Methods: We conducted a nationwide cross-sectional survey among Chinese residents aged over 12 years from June 20, 2022, to August 31, 2022. The Ocular Surface Disease Index-6 (OSDI-6) questionnaire was utilized to evaluate the presence of DES. Multivariable logistic regression models were used to analyze the associations between pet ownership and DES. Subgroup analyses were conducted based on sex, age, residence and affective disorders, and sensitivity analysis by excluding participants with major ocular diseases. The interactions between pet ownership and other risk factors on DES were explored in the additive scale by calculating the synergy index (SI). Results: A total of 21,916 subjects replied to the questionnaire. The prevalence of DES was 43.6 % (95 % confidence interval (CI), 43.0 %-44.3 %). Pet ownership was significantly associated with increased risk of DES (Odds ratio (OR): 1.13, 95%CI: 1.05-1.21), especially among the elderly (OR: 1.28, 95%CI: 1.09-1.51) and urban residents (OR: 1.13, 95%CI: 1.04-1.24). The individual effect of allergic rhinitis on DES was 2.59 (95%CI: 1.27-5.53), while the joint effect of pets and allergic rhinitis was 5.26 (95%CI: 1.20-36.74), suggesting a synergistic interaction with a SI of 2.48 (95%CI: 0.25-24.39). Furthermore, the interaction analysis also indicated a synergistic interaction between pet ownership and low health literacy with a SI of 1.12 (95%CI: 0.66-1.87). Conclusion: Pet ownership was identified as a risk factor for DES. The synergistic interaction of pet ownership and allergic rhinitis suggests shared mechanisms between DES and allergic conditions.